2016
DOI: 10.1002/adma.201506462
|View full text |Cite
|
Sign up to set email alerts
|

Freezing the Nonclassical Crystal Growth of a Coordination Polymer Using Controlled Dynamic Gradients

Abstract: A methodology that can be efficiently used to synthesize, isolate, and study out-of-equilibrium crystal structures employing controlled and diffusion-limited microfluidic environments is demonstrated. Unlike studies conducted with conventional mixing procedures in a flask, it is proven experimentally and with numerical simulations that microfluidic technologies can undoubtedly fine-tune reaction times and reagents concentration profiles; factors that enable out-of-equilibrium crystal forms to be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 43 publications
(47 reference statements)
0
31
0
Order By: Relevance
“…In 2016, the same group showed that not only 1D nanoscale CP structures are generated under RD conditions, but out-of-equilibrium CP crystal structures can also be accomplished [24]. In this study, the authors show that the microfluidic synthesis (under RD conditions) of a CP constructed from Cu(II) ions and 4,4 -bipyridine linkers leads to different crystal habits.…”
Section: Continuous Flowmentioning
confidence: 72%
“…In 2016, the same group showed that not only 1D nanoscale CP structures are generated under RD conditions, but out-of-equilibrium CP crystal structures can also be accomplished [24]. In this study, the authors show that the microfluidic synthesis (under RD conditions) of a CP constructed from Cu(II) ions and 4,4 -bipyridine linkers leads to different crystal habits.…”
Section: Continuous Flowmentioning
confidence: 72%
“…Accordingly, these results confirm that both Path A and Path B lead to the thermodynamically favoured CCP4 crystal form; however, the two paths are distinct and represent unique hiking routes in the free energy landscape of the system. It should also be noted that changes in the total flow rate (TFR) do not change the outcome, but simply the number of structures generated, 18 with an increase in FRR preventing the reaction from occurring (no MF-CCP-4 aggregates were observed by TEM imaging, see Methods section for further details).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, no depletion of reagents occurs during self-assembly, which in turn favours a fine control over self-assembly dynamics and growth pathways (vide infra). 18 This condition, for example, has been advantageously used to isolate and study kinetically-trapped species along a single crystallization pathway. 18 Note that even though other microfluidic methods (such as droplet-based microfluidic approaches) have been used to effectively synthetize MOF crystals in a continuous and faster manner, 19 RD conditions are only allowed by microfluidic devices operating under laminar flow regimes.…”
mentioning
confidence: 99%
See 2 more Smart Citations